2005
DOI: 10.4315/0362-028x-68.7.1336
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Orally Administered Salmonella enterica Serovars Agona and Montevideo in Atlantic Salmon (Salmo salar L.)

Abstract: The objective of our experiments was to study the persistence and dissemination of orally administered Salmonella in smoltified Atlantic salmon. In experiment 1, salmon kept at 15 degrees C were fed for 1 week with feed contaminated with 96 most-probable-number units of Salmonella Agona per 100 g of feed and then starved for 2 weeks. Samples were taken from the gastrointestinal tract and examined for Salmonella 1, 2, 8, 9, 15, and 16 days after the feeding ended. In experiment 2, Salmonella Agona and Montevide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Salmonella has also been found in the guts of river fish (Gaertner et al, 2008), and, via the gastrointestinal tract, entered the internal organs and muscle tissue in several freshwater species, e.g. rainbow trout (Salmo gairdneri), Israeli mirror carp (Cyprinus carpio) and tilapia (Tilapia aurea), and Atlantic salmon (Salmo salar) in saltwater (Nesse et al, 2005). Even marine mammals harbor Salmonella (Higgins, 2000).…”
Section: Salmonella In the Aquatic Environment And Live Fishmentioning
confidence: 98%
“…Salmonella has also been found in the guts of river fish (Gaertner et al, 2008), and, via the gastrointestinal tract, entered the internal organs and muscle tissue in several freshwater species, e.g. rainbow trout (Salmo gairdneri), Israeli mirror carp (Cyprinus carpio) and tilapia (Tilapia aurea), and Atlantic salmon (Salmo salar) in saltwater (Nesse et al, 2005). Even marine mammals harbor Salmonella (Higgins, 2000).…”
Section: Salmonella In the Aquatic Environment And Live Fishmentioning
confidence: 98%
“…Several studies observed the presence of Salmonella in fish and fishery products such as oysters (DePaola et al 2010) and in freshwater species, i.e. tilapia, rainbow trout, and carp (Nesse et al 2005). Fresh fish, fish meal, oysters and shrimp can carry Salmonella if they are caught in contaminated areas or processed in unsanitary conditions, and consumed raw or slightly cooked (Mol et al 2010, Norhana et al 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Aquarium water, for example, was the source of salmonellosis in a child (Senanayake et al 2004). Persistence and dissemination of salmonellae in fish were dependent on the number of salmonellae administered to the fish with high numbers required for their detection in intestines or muscles of the fish 4 weeks after administration (Buras et al 1985;Nesse et al 2005). In our previous study (Sha et al 2013), we demonstrated a fast decline of salmonellae in biofilms in time, which could be the basis for low percentages of salmonellae in both water and feces samples towards the end of the study, and also could explain the necessity to enrich for salmonellae cells so that they can be detected in low numbers in the intestine.…”
Section: Resultsmentioning
confidence: 99%